FREQUENCY OF SIGNIFICANT CORONARY ARTERY DISEASE IN CASES WITH ST SEGMENT DEPRESSION DURING RECOVERY PHASE OF EXERCISE - FAROOQ, U; ULLAH, N; QURESHI, AE; SAJJAD, M; ANUM, H; DAR, WA (Biological and Clinical Sciences Research Journal, 2023)
Coronary Artery Disease (CAD) imposes physical, social, and economic burden. It is amongst the leading causes of mortality and morbidity. Exercise-induced ST segment depression is considered reliable ECG finding for the diagnosis of obstructive coronary atherosclerosis. Exercise testing has an excellent safety record. The aim of the study is to determine the frequency of significant coronary artery disease in cases with ST-segment depression during recovery phase of exercise tolerance test. This descriptive case series was carried out at the Department of Cardiology, Rehmatul-Lil-Alamin Institute of Cardiology, Lahore, from 11-01-2021 to 10-07-2021. A total of 89 patients were taken in this study. Conventional coronary angiography via femoral or radial route was performed. Lesions were quantified by QCA technique in addition to visual assessment. Significant CAD was labelled as per operational definition. Patients ranged between 30-70 years of age with mean age of 51.8±10.8 years. There were 56 males (62.9%) while remaining 33 (37.1%) were females. History of diabetes mellitus was reported in 31 patients (34.8%), hypertension in 38 patients (42.7%) and smoking 51 (57.3%). Family history of CAD found in 46 patients (51.7%). Hyperlipidemia reported in 38 patients (42.7%). Significant CAD was observed in 76 patients (85.4%). Stratification for age, gender, diabetes mellitus, hypertension and smoking were carried out and found no association with significant CAD. In conclusion, 85.4% frequency rate of significant coronary artery disease in cases with ST segment depression during recovery phase of exercise tolerance test was observed. Thus, careful evaluation of ST segment depression occurring in recovery phase may add significantly to the clinical information derived from the results of ETT.